2019
DOI: 10.1186/s12911-019-0898-5
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pros and cons – developing a patient decision aid to cultivate dialog to build relationships: insights from a qualitative study and decision aid development

Abstract: Background An individualized approach using shared decision-making (SDM) and goal setting is a person-centred strategy that may facilitate prioritization of treatment options. SDM has not been adopted extensively in clinical practice. An interprofessional approach to SDM with tools to facilitate patient participation may overcome barriers to SDM use. The aim was to explore decision-making experiences of health professionals and people with diabetes (PwD), then develop an intervention to facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…We previously reported on how the development and refinement of MyDiabetesPlan , an interprofessional shared decision-making (IPSDM) toolkit, following the principles of user-centered design [ 19 , 20 ]. In this paper, we describe our assessment of the effectiveness of MyDiabetesPlan through a two-step cluster RCT followed by individual interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported on how the development and refinement of MyDiabetesPlan , an interprofessional shared decision-making (IPSDM) toolkit, following the principles of user-centered design [ 19 , 20 ]. In this paper, we describe our assessment of the effectiveness of MyDiabetesPlan through a two-step cluster RCT followed by individual interviews.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the first step was provider-directed ( MyDiabetesPlan was delivered to physicians, nurses, dietitians , or pharmacists), whereas the second step (occurring 6 months later) was provider- and patient-directed (patients were asked to use MyDiabetesPlan by themselves before the appointment; this was then reviewed by the provider team). We chose a two-step approach because a prior feasibility study [ 20 ] identified that patients required clinician assistance for completing their initial MyDiabetesPlan . Outcome measures were administered at the first step (baseline), second step (6 months later), and follow-up (12 months later).…”
Section: Methodsmentioning
confidence: 99%
“…[ 39 ]). There were no definitions or conceptualisation of public involvement in almost half of articles ( n = 43, 46.2%) [ 40 – 82 ]. Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were no definitions or conceptualisation of public involvement in almost half of articles ( n = 43, 46.2%) [ 40 – 82 ]. Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ]. Some authors provided demographic data of public participants, such as age, gender, medical condition and/or race, however, there was no detail provided in more than half of articles ( n = 52, 55.9%) [ 37 , 38 , 40 , 41 , 43 – 51 , 55 , 58 , 59 , 61 , 63 , 66 , 68 , 69 , 71 74 , 77 , 79 , 81 – 88 , 93 , 95 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants were keen to be involved in decision making and identified the doctor as the key healthcare professional to advocate and advise on CRC screening. A trusting doctor-patient relationship is the cornerstone in SDM [ 35 ]. It is imperative for doctors to modify their consultation style from a paternalistic approach to SDM.…”
Section: Discussionmentioning
confidence: 99%